Pathways to survival: Identifying psychosocial, family and service mechanisms to improve anti-retroviral adherence amongst adolescents living with HIV in Southern Africa - Cluver, L; Toska, E; Hodes, R; Orkin, M; Gardner, F; Boyes, M; Sherr, L; Casale, M; Carty, C; Gittings, L; Langwenya, N; Natukunda, H; et al. (2019)
This report summarises the study findings and impact of a research project implemented jointly by the Universities of Oxford and Cape Town: Pathways to survival: identifying psychosocial, family and service mechanisms to improve anti-retroviral adherence amongst HIV-positive adolescents in Southern Africa (hereafter: Mzantsi Wakho – Your South Africa – its locally used name). The core source of funding for this high-impact and successful study came from the Nuffield Foundation. This study was also supported by supplementary co-funding. This study was the first to systematically examine potential causes of ART non-adherence and non-retention in HIV care amongst adolescents (10-19 years old) in Sub-Saharan Africa. Through additional funding awarded to the research team, additional research aims were also examined. The research project was implemented by a team of more than 50 researchers, including capacity-building for early-career academics and students in South Africa and the UK. In July 2015 – March 2018, this multi-disciplinary, mixed-methods team engaged with over 1,600 adolescents, 100 caregivers, and 120 healthcare providers through participatory workshops, in-depth interviews, ethnographic research, and three waves of quantitative surveys. In parallel, a clinic team engaged with over 79 public health facilities collecting data from clinic managers, healthcare providers, and patient files (with appropriate consent). With the essential support of the Nuffield Foundation, this study became the world’s largest longitudinal cohort of adolescents living with HIV. Mzantsi Wakho’s research team successfully followed up and maintained high retention rates across three time points, as research participants transitioned from early adolescence into youth. The study has already had major impact on policy, UN guidelines and programming for adolescents living with HIV.